2006
DOI: 10.1007/bf03345555
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and nitric oxide

Abstract: Melatonin is a product of the amino acid tryptophan in the pineal gland. Once synthesized, the specific mechanisms governing the release of melatonin from the pineal gland and its functions are largely unknown. Besides its regulatory role in circadian rhythms in mammals, because of its widespread subcellular distribution, melatonin contributes to the reduction of oxidative damage in both the lipid and the aqueous environments of the cell. This postulate is widely supported by the experimental observations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(51 citation statements)
references
References 50 publications
4
46
0
1
Order By: Relevance
“…• and NOO • formation and thus prevents polyunsaturated fatty acid oxidation (Teixeira et al 2003;Aydogan et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…• and NOO • formation and thus prevents polyunsaturated fatty acid oxidation (Teixeira et al 2003;Aydogan et al 2006). …”
Section: Discussionmentioning
confidence: 99%
“…It can protect cells against hydroxyl radicals (the most frequent type of free radical following irradiation), hydrogen peroxide, nitric oxide (a product by immune cells), peroxynitrite anion, and singlet oxygen (Chetsawang et al 2006;Cagnoli et al 1995;Aydogan et al 2006). Also, melatonin ameliorates oxidative stress at different levels, such as modulation of molecular pathways and cellular functions that are explained in detail below.…”
Section: Antioxidative Effects Of Melatoninmentioning
confidence: 99%
“…Inhibition of NO production may be a further means whereby melatonin reduces oxidative damage under conditions, such as in ischemia/reperfusion and sepsis, where NO seems to be important in terms of the resulting damage [43]. Previously, we have shown that melatonin can promote neuronal differentiation [41,44].…”
Section: Role Of Melatonin In the Inhibition Of Nox Releasementioning
confidence: 99%